Edukasi Tentang Gout Arthritis Sebagai Upaya Kesadaran Dan Pencegahan Penyakit Asam Urat Di Desa Pasar X Dusun 3 - Alfathin, Adnan Andisyah; Rahman, Shahrul (Jurnal Ilmiah Wahana Pendidikan, 2025)
Gout arthritis, or gout, is a joint disorder caused by the buildup of uric acid crystals in the body. This disease often has a negative impact on sufferers' quality of life, with the main symptoms being severe joint pain and inflammation. In the village of Pasar This article aims to educate the public about gout arthritis as an effort to increase awareness and prevent gout. Through health education and education, it is hoped that the public can understand risk factors, such as a high-purine diet, alcohol consumption and obesity, and adopt a healthy lifestyle. With better knowledge, it is hoped that society can be more proactive in preventing and managing gouty arthritis, as well as improving overall health.